1998
DOI: 10.1128/aac.42.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grapefruit Juice on Clarithromycin Pharmacokinetics

Abstract: To investigate whether grapefruit juice inhibits the metabolism of clarithromycin, 12 healthy subjects were given water or grapefruit juice before and after a clarithromycin dose of 500 mg in a randomized crossover study. Administration of grapefruit juice increased the time to peak concentration of both clarithromycin (82 ± 35 versus 148 ± 83 min; P = 0.02) and 14-hydroxyclarithromycin (84 ± 38 min versus 173 ± 85;P = 0.01) but did not affect other pharmacokinetic parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…For CLR, a single dose cross-over design study showed that food intake directly before intake of a CLR tablet increased the extent of absorption by 25% and increased the AUC of the metabolite of CLR by approximately 9% [147]. An open-label cross-over study of 12 healthy volunteers showed that grapefruit juice, a well-known inhibitor of intestinal CYP3A4, had no effect on CLR PK parameters, except for an increased t max [148]. For erythromycin (ERY) acistrate and enterocoated ERY bases the authors of a randomized cross-over study concluded that food intake had no effect on the PK of ERY acistrate and a slight effect on steady-state PK of the enterocoated ERY bases that might have some clinical relevance [149].…”
Section: Resultsmentioning
confidence: 99%
“…For CLR, a single dose cross-over design study showed that food intake directly before intake of a CLR tablet increased the extent of absorption by 25% and increased the AUC of the metabolite of CLR by approximately 9% [147]. An open-label cross-over study of 12 healthy volunteers showed that grapefruit juice, a well-known inhibitor of intestinal CYP3A4, had no effect on CLR PK parameters, except for an increased t max [148]. For erythromycin (ERY) acistrate and enterocoated ERY bases the authors of a randomized cross-over study concluded that food intake had no effect on the PK of ERY acistrate and a slight effect on steady-state PK of the enterocoated ERY bases that might have some clinical relevance [149].…”
Section: Resultsmentioning
confidence: 99%
“…[15,16]. P-glycoprotein (Pgp) which is also expressed in the brush border membrane of the small intestine, appears to play a considerable role in mechanisms of first-pass extractions of drugs, as recently reviewed [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating the bioavailability of clarithromycin and telithromycin in rats demonstrated that the limited oral bioavailability is primarily due to low intestinal availability rather than first‐pass metabolism in the liver . In addition, grapefruit juice, a selective intestinal CYP3A4 inhibitor, did not significantly affect the oral absorption of clarithromycin or telithromycin . These findings indicate that P‐gp efflux in the intestinal epithelial cells plays a larger role than first‐pass metabolism for the limited intestinal permeability .…”
Section: Discussionmentioning
confidence: 67%